2009
DOI: 10.1002/pssb.200982253
|View full text |Cite
|
Sign up to set email alerts
|

Study on cellular adhesion of human osteoblasts on nano‐structured diamond films

Abstract: The need of new biocompatible materials with superior properties and flexibility in their surface termination and functionalization for medical applications is constantly increasing. Due to the combination of intrinsic properties, chemically deposited diamond thin films are proposed as one of the most promising material in this field. They are chemically/ mechanically/physically stable and their surface can be modified by a variety of chemical or plasmatic techniques. In the present work, different diamond nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…The structured films are required for applications like protective layers on transistors [7] or advanced hybrid MEMS devices [8]. The micro-structured diamond films are also used for tissue engineering [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The structured films are required for applications like protective layers on transistors [7] or advanced hybrid MEMS devices [8]. The micro-structured diamond films are also used for tissue engineering [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the behavior of different cell types on nanodiamond films shows that they react differently according to surface smoothness [55,57,60,68,77,78]. Scanning electron microscopy (SEM) and immunofluorescence staining examinations of osteoblast on nanodiamond films with various surface roughness (nanometer and micrometer) generally demonstrated that enhanced osteoblast functions (including adhesion, proliferation, www.intechopen.com intracellular protein synthesis, alkaline phosphatase activity and extracellular calcium deposition) on nanocrystalline diamond (RMS~20 nm) compared to submicron diamond grain size films and control for all time periods tested up to 21 days [57,60].…”
Section: Topography Effects Of Nanodiamond Films On Cellsmentioning
confidence: 99%
“…Numerous studies using immunefluorescent staining have shown the presence of vinculin and pY397 focal adhesion kinase (FAK) in cultured human osteoblasts on nanostructured diamond films [60,78,79]. The osteoblasts adhered on ultra nano-cones and nano-cones, showing large focal adhesions and relatively strong activation of FAK, are thus more predestined for successful colonization of the entire environment [60,78]. Hamilton [90] suggested that osteoblast response to substrates with specific topographical features requires FAK-Y397-Src-Y416 complexes for ERK1/2 phosphorylation.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The diamonds films structuring into form of nano-rods (Fig. 2c) was reported previously [23] and represent the morphology that stimulates cells differentiation [24].…”
mentioning
confidence: 92%
“…In the case of fully oxidized NCD surfaces, only oxygen plasma treatment was involved to process the films [24,25].…”
mentioning
confidence: 99%